The Influence of Work Discipline and Supervision on Work Performance with Job Satisfaction as an Intervening Variable in the Women's Empowerment Service for Child and Community Protection in Binjai City - Yanti Rawi, Mira; Isa Indrawan, Muhammad (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of work discipline and supervision on work performance with job satisfaction as an intervening variable. This research was conducted at the Women's Empowerment, Child and Community Protection Office, Binjai City. The population in this study was 80 employees and the sample used was saturated sample technique. Data collection was carried out by distributing questionnaires. Sources of research data using primary data sources. The research model used is path analysis and the measurement tool is Samart PLS version 3.3.3. The results of the study are as follows: Work Discipline has a positive and significant effect on Job Satisfaction. Work Discipline has a positive and significant effect on work performance. Job satisfaction has a positive and significant effect on work performance. Supervision has a positive and significant effect on job satisfaction. Supervision has a positive but not significant effect on work performance. Work Discipline influences Work Performance and Job Satisfaction and can become an intervening variable for Work Discipline and Work Performance. Supervision has an effect on Job Performance and Job Satisfaction capable of being an intervening for Supervision and Work Performance.